Development of E-Module Media on Learning to Make Body Proportion Images in Class X Fashion Design SMK Negeri 1 Buduran - Adani, Marsha Belinda; Rahayu, Imami Arum Tri; Arifiana, Deny; Mayasari, Peppy (PT. Riset Press International, 2024)
Media Learning is an educational instrument to support the learning process. The purpose of this study is to determine the process of developing E-Module media, the feasibility level of E-Module media, and student learning outcomes after applying E-Module media to learning to make body proportion images. This research uses Research and Development (R&D) research with the ADDIE development model. The data collection technique used feasibility validation with 2 media validation experts and 2 material validations as well as tests by students in class X fashion with a total of 36 students. The data analysis technique used is an assessment of media feasibility and student learning outcomes. The results of the E-Module media feasibility level research on learning to make body proportion images were declared very feasible with a score of 4.25. Student learning outcomes in learning to make body proportion drawings are shown with classical percentages of 97% complete and 3% incomplete. E-Module learning media with very feasible categories can improve student learning outcomes in learning to make body proportion images in class X of SMK Negeri 1 Buduran.